DAMPAK STATUS IMUNISASI ANAK BALITA DI INDONESIA TERHADAP KEJADIAN PENYAKIT - Lestari, C.S. Whinie; Tjitra, Emiliana; Sandjaja, Sandjaja (Badan Penelitian dan Pengembangan Kesehatan, 2009)
Immunization protects its immunized and related or concomitant diseases. Though Indonesia was reported has reached the target of Universal Child Immunization (UCI) in 1990, in reality still be reported measles outbreaks. Hence it was needed more data to explain this issue. The 2007-2008 Baseline Health Research collected immunization data from the community. We extend analysing immunization data to identify and determine factors influence the immunization program and immunization impact, using complex samples by SPSS 15. Of the 258,466 households in Baseline Health Research, there is recorded 61,843 children under 5 years old. The result extend analysis coverage of completed basic immunization in children 12-59 months is reported only 41.4% (28,644 of 69,189). In contrary, a high coverage is recorded in measles immunization (81.3%, 50,278 of 61,843) . There is also significant higher proportion (5.3%) of measles reported in children who did not get measles immunization compare to children with measles immunization (3.5%). The risk of suffering measles with pneumonia, and measles with pneumonia and diarrhea are 2.4 times and 2.7 times (p<0.01) in children who did not get completed basic immunization compare to children with completed basic immunization. Conclusion of extend analysis shows that measles immunization is not a good predictor for having completed basic immunization status in children. Measles immunization is still effective to prevent measles and its complications. Nutritional status of children 12-59 months is also associated with the status of completed immunization. The most influenced factors to the status of completed basic immunization are the education of headfamily and utility of health services. Key words : Children 12-59 Months, Immunization, Measles, Pneumonia, Diarrhea, Nutritional Status